CaPTure: Calcium PeakToolbox for analysis of in vitro calcium imaging data - Madhavi Tippani; Elizabeth A. Pattie; Brittany A. Davis; Claudia V. Nguyen; Yanhong Wang; Srinidhi Rao Sripathy; Brady J. Maher; Keri Martinowich; Andrew E. Jaffe; Stephanie Cerceo Page (BMC Neuroscience, 2022)
Abstract Background Calcium imaging is a powerful technique for recording cellular activity across large populations of neurons. However, analysis methods capable of single-cell resolution in cultured neurons, especially for cultures derived from human induced pluripotent stem cells (hiPSCs), are lacking. Existing methods lack scalability to accommodate high-throughput comparisons between multiple lines, across developmental timepoints, or across pharmacological manipulations. Results To address this need we developed CaPTure, a scalable, automated Ca2+ imaging analysis pipeline ( https://github.com/LieberInstitute/CaPTure ). CaPTuredetects neurons, classifies and quantifies spontaneous activity, quantifies synchrony metrics, and generates cell- and network-specific metrics that facilitate phenotypic discovery. The method is compatible with parallel processing on computing clusters without requiring significant user input or parameter modification. Conclusion CaPTure allows for rapid assessment of neuronal activity in cultured cells at cellular resolution, rendering it amenable to high-throughput screening and phenotypic discovery. The platform can be applied to both human- and rodent-derived neurons and is compatible with many imaging systems.